Rare earth element reinforced silicon carbide ceramic wave-absorbing material and preparation method thereof

By using a single-layer continuous silicon carbide fiber braid with rare earth elements reinforced in ceramic absorbing materials, and through the preparation method of high-temperature cracking and densification, the problems of the decrease in strength and deterioration of thermal properties of ceramic absorbing materials at high temperatures are solved, and the problem of decrease in strength and deterioration of thermal properties at high temperatures is achieved. Improved high temperature strength and thermal stability.

CN119462160APending Publication Date: 2025-02-18GUIZHOU BOTAO ELECTRONIC TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411704881.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The problems of the decline in strength and deterioration of thermal properties of existing ceramic wave absorbing materials at high temperatures.

Method used

A single-layer continuous silicon carbide fiber braid is made of rare earth elements, and impregnated by an impregnation solution prepared by polycarbosilane, xylene and rare earth elements, and then undergoes high-temperature cracking and densification.

Benefits of technology

It improves the high temperature strength and thermal stability of ceramic wave absorbing materials, enhances its absorbing performance and densification degree, and solves the problems of high brittleness and easy breakage in traditional ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462160A_ABST
    Figure CN119462160A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wave-absorbing materials, and particularly discloses a rare earth element reinforced silicon carbide ceramic wave-absorbing material and a preparation method thereof, the rare earth element reinforced silicon carbide ceramic wave-absorbing material comprises a single-layer continuous silicon carbide fiber woven body, and the length, width and height of the single-layer continuous silicon carbide fiber woven body are 180mm * 180mm * 2mm. Single-layer continuous silicon carbide fiber weaving is densified through pretreatment, dipping and high-temperature cracking. As silicon carbide is a strong covalent compound and has low atomic diffusivity, the silicon carbide is difficult to sinter compactly at high temperature, while an outer layer electronic structure of the rare earth element has high complexity and outer layer electron transition is more difficult, so that the high temperature resistance is more excellent; the high-temperature performance and the thermal stability of the silicon carbide ceramic wave-absorbing material can be improved through various mechanisms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wave-absorbing materials, and in particular to a rare earth element reinforced silicon carbide ceramic wave-absorbing material and a preparation method thereof. Background Art

[0002] Since ceramic absorbing materials have the multifunctionality of high temperature resistance, light weight, stealth performance and electromagnetic protection, they are widely used in aerospace, military protection and electronic communications. With the rapid development of these fields, the demand for ceramic absorbing materials is increasing. In order to further improve its stealth performance, meet the lightweight requirements, improve weather resistance and stability, and adapt to the multifunctional requirements, it is necessary to enhance the ceramic absorbing materials. At present, there are two main ways to enhance ceramic absorbing materials. One is to use ceramic particles as absorbents and use hot pressing technology to prepare particle-reinforced ceramic materials, such as Si / C / N ceramic particles reinforced LAS glass, mullite, Si3N4 and other ceramic materials, but such materials have narrow radar absorption bands, poor toughness of particle-reinforced ceramic materials, prone to catastrophic damage, and difficult to prepare large and complex components by hot pressing technology. The other is SiC continuous fiber reinforced ceramic matrix multilayer composite materials. Because such materials have the advantages of wide radar absorption bands, high strength, high toughness, and easy to form large and complex components, they have become the key research direction of ceramic absorbing materials.

[0003] However, silicon carbide is a strong covalent compound with low atomic diffusion capacity, so it is difficult to sinter densely at high temperatures. In order to promote the sintering densification effect and reduce the sintering temperature, it is usually necessary to add high-temperature sintering aids, such as compounds such as polycarbosilane and xylene. Since additives such as polycarbosilane and xylene may decompose or react with other components at high temperatures to generate new phases or impurities, these new phases or impurities may be distributed at the silicon carbide grain boundaries or inside the grains, affecting the overall structure of the material, thereby reducing its high-temperature strength. If the additive forms a liquid phase at high temperatures, although it helps to reduce the sintering temperature and improve density, too much liquid phase may cause the material to deform or crack at high temperatures, thereby reducing its high-temperature strength and thermal properties. Summary of the invention

[0004] The purpose of the present invention is to provide a rare earth element reinforced silicon carbide ceramic absorbing material and a preparation method thereof, so as to solve the problem that the use of existing polycarbosilane and xylene causes the high temperature strength of silicon carbide ceramic absorbing materials to decrease and the thermal properties to deteriorate.

[0005] In order to solve the above problems, the technical solutions provided are as follows:

[0006] A rare earth element reinforced silicon carbide ceramic absorbing material, the ceramic absorbing material comprises a single-layer continuous silicon carbide fiber braid, the single-layer continuous silicon carbide fiber braid has a length, width and height of 180mm*180mm*2mm, and the single-layer continuous silicon carbide fiber braid is impregnated with an impregnation liquid prepared with polycarbosilane, xylene and rare earth elements, and then subjected to high-temperature cracking.

[0007] The basic principle and beneficial effect of the above scheme are: compared with the existing SiC continuous fiber reinforced ceramic-based multilayer composite materials, this technical scheme adopts a single-layer continuous silicon carbide fiber braid. The resistivity of the single-layer continuous silicon carbide fiber braid is 104Ω·cm. Continuous silicon carbide fiber is known for its high strength and high toughness. It can effectively improve the bearing capacity of the ceramic matrix, making the composite material more stable and reliable when subjected to external forces. This reinforcement effect helps to solve the problem of traditional ceramic materials being brittle and easy to break.

[0008] A method for preparing the rare earth element reinforced silicon carbide ceramic absorbing material according to claim 1, comprising the following steps:

[0009] S1: Pretreatment: Place a single-layer continuous silicon carbide fiber braid with a length, width and height of 180mm*180mm*2mm in a baking oven at a temperature of 500-600℃ and bake for 2h;

[0010] S2: Impregnation: prepare a solution of polycarbosilane, xylene and rare earth elements in a weight ratio of 1:(1-3):(0.01-0.1), use this solution as a precursor impregnation solution, place the pretreated single-layer continuous silicon carbide fiber braid into the impregnation solution and immerse for 1-2 hours;

[0011] S3: High temperature cracking: The impregnated single-layer continuous silicon carbide fiber braid is placed in high-purity nitrogen at a temperature of 800-1200°C for 0.5-1h for single cracking and densification.

[0012] The basic principle and beneficial effects of the above scheme are: since silicon carbide is a strong covalent compound with low atomic diffusion ability, it is difficult to sinter densely at high temperatures, and the outer electron structure of rare earth elements is highly complex, and outer electron transitions are more difficult, making the high temperature resistance more excellent. By adding rare earth elements to the impregnation precursor solution, the high temperature performance of silicon carbide ceramic absorbing materials can be improved through a variety of mechanisms, including increasing the degree of densification, inhibiting grain growth, improving thermal properties, and improving absorbing performance. In addition, rare earth elements are added to polycarbosilane and xylene, and it is not easy to form a liquid phase at high temperatures, thereby improving high temperature strength and improving thermal stability.

[0013] Furthermore, in step S2, the weight ratio of polycarbosilane, xylene and rare earth element is 1:2:0.04.

[0014] Furthermore, the impregnation liquid in step S2 is prepared by stirring in a high-speed stirrer at a rotation speed of 1000-2000 r / min for 10-20 minutes.

[0015] Furthermore, the cracking temperature of step S3 is 1000°C.

[0016] Furthermore, the cracking and densification in step S3 is performed multiple times, a total of 7 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a process flow chart of enhancing silicon carbide ceramic absorbing material of the present invention;

[0018] Figure 2 This is a reflectivity curve of the ceramic absorbing material of Example 1 in the frequency band of 8 GHz to 18 GHz at room temperature;

[0019] Figure 3 This is a reflectivity curve of the ceramic absorbing material of Example 2 in the frequency band of 8 GHz to 18 GHz at room temperature;

[0020] Figure 4 This is a reflectivity curve of the ceramic absorbing material of Example 3 in the frequency band of 8 GHz to 18 GHz at room temperature;

[0021] Figure 5 This is a reflectivity curve of the ceramic absorbing material of Example 4 in the frequency band of 8 GHz to 18 GHz at room temperature; DETAILED DESCRIPTION

[0022] The following is further described in detail through specific implementation methods:

[0023] The embodiment is basically as shown in the attached Figure 1-5 As shown:

[0024] The specific implementation process is as follows:

[0025] Example 1

[0026] S1: Pretreatment: Place a single-layer continuous silicon carbide fiber braid with a length, width and height of 180mm*180mm*2mm in a 500℃ oven for 2 hours to reduce the thermal stress inside the fiber;

[0027] S2: Impregnation: Put polycarbosilane and xylene in a weight ratio of 1:2 into a stirring barrel, stir for 20 minutes at a speed of 1500r / min to prepare a solution, which is used as a precursor impregnation liquid. Transfer the impregnation liquid from the stirring barrel to a 300mm*300mm*50mm plastic frame, and place the pretreated single-layer continuous silicon carbide fiber braid into the impregnation liquid for 1.5 hours;

[0028] S3: High temperature cracking: The impregnated single-layer continuous silicon carbide fiber braid is placed in a high temperature cracking furnace containing high-purity nitrogen at a temperature of 1200°C for 0.8h for single cracking and densification, and the cracking and densification cycles are repeated a total of 7 times.

[0029] The performance parameters of the silicon carbide fiber reinforced silicon carbide ceramic absorbing material of Example 1 were tested. The reflectivity of the strong ceramic absorbing material was tested in the 8 GHz to 18 GHz frequency band by the bow frame method. The density of the ceramic absorbing material was tested by the Archimedes method. The test results are shown in Table 1 below. The test curve is shown in the following table. Figure 2 As shown:

[0030] Table 1: Main performance parameters of the ceramic absorbing material of Example 1

[0031]

[0032] Example 2

[0033] S1: Pretreatment: Place a single-layer continuous silicon carbide fiber braid with a length, width and height of 180mm*180mm*2mm in a 500℃ oven for 2 hours to reduce the thermal stress inside the fiber;

[0034] S2: Impregnation: Put polycarbosilane, xylene and yttrium nitrate in a weight ratio of 1:2:0.04 into a stirring barrel, stir for 20 minutes at a speed of 1500r / min to prepare a solution, which is used as a precursor impregnation solution. Transfer the impregnation solution from the stirring barrel to a 300mm*300mm*50mm plastic frame, and place the pretreated single-layer continuous silicon carbide fiber braid into the impregnation solution for 1.5 hours;

[0035] S3: High temperature cracking: The impregnated single-layer continuous silicon carbide fiber braid is placed in a high temperature cracking furnace containing high purity nitrogen at a temperature of 1000°C for 0.8h for single cracking and densification, and the cracking and densification cycles are a total of 7 times.

[0036] The performance parameters of the silicon carbide fiber reinforced silicon carbide ceramic absorbing material of Example 2 were tested. The reflectivity of the strong ceramic absorbing material was tested in the 8 GHz to 18 GHz frequency band by the bow frame method. The density of the ceramic absorbing material was tested by the Archimedes method. The test results are shown in Table 2 below. The test curve is shown in the following table. Figure 3 As shown:

[0037] Table 2: Main performance parameters of the ceramic absorbing material of Example 2

[0038]

[0039] Example 3

[0040] S1: Pretreatment: Place a single-layer continuous silicon carbide fiber braid with a length, width and height of 180mm*180mm*2mm in a 500℃ oven for 2 hours to reduce the thermal stress inside the fiber;

[0041] S2: Impregnation: Put polycarbosilane, xylene and lanthanum nitrate in a weight ratio of 1:2:0.04 into a stirring barrel, stir for 20 minutes at a speed of 1500r / min to prepare a solution, which is used as a precursor impregnation liquid. Transfer the impregnation liquid from the stirring barrel to a 300mm*300mm*50mm plastic frame, and place the pretreated single-layer continuous silicon carbide fiber braid into the impregnation liquid for 1.5 hours;

[0042] S3: High temperature cracking: The impregnated single-layer continuous silicon carbide fiber braid is placed in a high temperature cracking furnace containing high purity nitrogen at a temperature of 1000°C for 0.8h for single cracking and densification, and the cracking and densification cycles are a total of 7 times.

[0043] The performance parameters of the silicon carbide fiber reinforced silicon carbide ceramic absorbing material of Example 1 were tested. The reflectivity of the strong ceramic absorbing material was tested in the 8 GHz to 18 GHz frequency band by the bow frame method. The density of the ceramic absorbing material was tested by the Archimedes method. The test results are shown in Table 3 below. The test curve is shown in the following table. Figure 4 As shown:

[0044] Table 3: Main performance parameters of the ceramic absorbing material of Example 3

[0045]

[0046] Example 4

[0047] S1: Pretreatment: Place a single-layer continuous silicon carbide fiber braid with a length, width and height of 180mm*180mm*2mm in a 500℃ oven for 2 hours to reduce the thermal stress inside the fiber;

[0048] S2: Impregnation: Put polycarbosilane, xylene, yttrium nitrate and lanthanum nitrate in a weight ratio of 1:2:0.01:0.03 into a stirring barrel, stir for 20 minutes at a speed of 1500r / min to prepare a solution, transfer the impregnation liquid from the stirring barrel to a 300mm*300mm*50mm plastic frame, use this solution as a precursor impregnation liquid, place the pretreated single-layer continuous silicon carbide fiber braid into the impregnation liquid and immerse for 1.5 hours;

[0049] S3: High temperature cracking: The impregnated single-layer continuous silicon carbide fiber braid is placed in a high temperature cracking furnace containing high purity nitrogen at a temperature of 900°C for 0.8h for single cracking and densification, and the cracking and densification cycles are repeated a total of 7 times.

[0050] The performance parameters of the silicon carbide fiber reinforced silicon carbide ceramic absorbing material of Example 1 were tested. The reflectivity of the strong ceramic absorbing material was tested in the 8 GHz to 18 GHz frequency band by the bow frame method. The density of the ceramic absorbing material was tested by the Archimedes method. The test results are shown in Table 4 below. The test curve is shown in Table 4 below. Figure 5 As shown:

[0051] Table 4: Main performance parameters of the ceramic absorbing material of Example 4

[0052]

[0053] The main performance parameters of the ceramic absorbing materials in Tables 1-4 are summarized in Table 5 below:

[0054]

[0055] From the data results in Table 5 above and Figure 2-5 It can be concluded from the curve that adding rare earth elements to the impregnation precursor solution can improve the high temperature performance of silicon carbide ceramic absorbing materials through various mechanisms, including increasing the degree of densification, inhibiting grain growth, improving thermal properties, and improving absorbing performance. In addition, rare earth elements added to polycarbosilane and xylene are not easy to form a liquid phase at high temperature, thereby improving high temperature strength and thermal stability.

[0056] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A rare earth element reinforced silicon carbide ceramic absorbing material, characterized in that: The ceramic wave absorbing material comprises a single-layer continuous silicon carbide fiber braid, the length, width and height of the single-layer continuous silicon carbide fiber braid is 180mm*180mm*2mm, the single-layer continuous silicon carbide fiber braid is impregnated with an impregnation liquid prepared with polycarbosilane, xylene and rare earth elements, and then undergoes high-temperature cracking.

2. A method for preparing the rare earth element reinforced silicon carbide ceramic absorbing material according to claim 1, characterized in that: The following steps are involved: S1: Pretreatment: Place a single-layer continuous silicon carbide fiber braid with a length, width and height of 180mm*180mm*2mm in a baking oven at a temperature of 500-600℃ and bake for 2 hours; S2: Impregnation: prepare a solution of polycarbosilane, xylene and rare earth elements in a weight ratio of 1:(1-3):(0.01-0.1), use this solution as a precursor impregnation solution, place the pretreated single-layer continuous silicon carbide fiber braid into the impregnation solution and immerse for 1-2 hours; S3: High temperature cracking: The impregnated single-layer continuous silicon carbide fiber braid is placed in high-purity nitrogen at a temperature of 900-1200°C for 0.5-1h for single cracking and densification.

3. The method for preparing a rare earth element reinforced silicon carbide ceramic absorbing material according to claim 2, characterized in that: In the step S2, the weight ratio of polycarbosilane, xylene and rare earth element is 1:2:0.

04.

4. The method for preparing a rare earth element reinforced silicon carbide ceramic absorbing material according to claim 3, characterized in that: The impregnation liquid in step S2 is prepared by stirring in a high-speed stirrer at a rotation speed of 1000-2000 r / min for 10-20 minutes.

5. The method for preparing a rare earth element reinforced silicon carbide ceramic absorbing material according to claim 4, characterized in that: The cracking temperature of step S3 is 1000°C.

6. The method for preparing a rare earth element reinforced silicon carbide ceramic absorbing material according to claim 5, characterized in that: The step S3 is performed for multiple times of cracking and densification, 7 times in total.

Citation Information

Patent Citations

  • Silicon carbide composite wave absorbing ceramic based on metamaterial and preparation method of silicon carbide composite wave absorbing ceramic

    CN106220211A

  • Preparation method of rare earth oxide modified C / (C-) SiC-ZrC composite material

    CN116178051A

  • Method for preparing silicon carbide fiber reinforced silicon carbide composite material

    CN1803715A

  • Ceramic composite material and its production method

    JP2006265080A

  • Preparation method of micro-area in-situ reaction of ceramic-based composite material reinforced with high strength fibre

    WO2013060175A1